Etnografia em quadrinhos: subjetividades e escrita de si Tembé-Tentetehara - OLIVEIRA JUNIOR, Otoniel Lopes de (Universidade Federal do Pará, 2018)
Comics is a language that uses textual and pictorial resources for production of meaning. More than just the sum of these resources, comics is a noteworthy hybrid with unique expressive features to production of discourse and statements. As a vehicle of cultural industry, but not only contained in it, the comic play a dual role, at the same time they act as mass media, it's also a language that through its conditions of its historical possibilities, provide the appearance of subjects knowledges. Historically, Brazilian indigenous societies undergo a process of adjustment to a homogeneous culture colonialism, be it historical, be it cultural, be it ethnic genocide. The representation of brazilian’s indigenous in materiality of the cultural industry is commonly marked by standardization of subjectivity and stereotyping images. Presenting the language of comics and their characteristics, this paper will examine, through archgeneological method if such subjective processes of indigenous peoples are present in a materiality clipping comic produced in the cultural industry. Also discuss the process of emergence of indigenous subjects knowledges by Tembe-Tenetehara's statements in comic language, made from workshops held in the Aldeia Sede as part of a participative field research presented here through a ethnography draw and comics.